Grammatical and Lexical Challenges in Writing Descriptive Text: A Case Study of the Seventh-Grade Students at SMP Negeri 15 Denpasar - Dewi, Anak Agung Putri Kusuma (UICELE, 2026)
Although several research has examined the challenges in writing descriptive text, still limited attention in grammatical and lexical challenges in writing descriptive text. To close this gap, this study aimed to analyze students’ challenges in writing descriptive text and identify factors influence those challenges. The data were collected from 35 seventh grade students at SMPN 15 Denpasar using content analysis and interviews. The data were analyzed using qualitative data analysis from Miles and Huberman (2014). The findings shown that grammatical challenges appeared are verb, pronoun, auxiliary, adjective, tenses, article, preposition, spelling and subject verb agreement, then the lexical challenges appeared are collocation, word meaning, word form and appropriate word use in context. Furthermore, the factors influenced students’ challenges come from internal factors included low self-confident, limited grammar knowledge, lexical knowledge, and poor in writing habits. Then external factors included lack of reading habits, limited writing practice, teaching method, learning materials, classroom environment, and time limitation. These findings provide valuable insights for English teachers in designing effective teaching strategies and assessment practice to improve students grammatical and lexical challenges in writing descriptive text. Thus, the study contributes to development of instructional design and assessment in English Language Teaching (ELT).